2021
DOI: 10.3390/genes12020261
|View full text |Cite
|
Sign up to set email alerts
|

Precision Surgery and Kidney Cancer: Knowledge of Genetic Alterations Influences Surgical Management

Abstract: Renal cell carcinoma is a term that represents multiple different disease processes, each driven by different genetic alterations, with distinct histology, and biological potential which necessitates divergent management strategies. This review discusses the genetic alterations seen in several forms of hereditary kidney cancer and how that knowledge can dictate when and how to intervene with a focus on the surgical management of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…When tumors are relatively small and localized, unique surgical approaches for FH-deficient RCC can be taken. These include immediate resection upon observation, partial nephrectomy with wider margins or radical nephrectomy, regional lymph node dissection, and/or open surgery (11)(12)(13)(14)(15). Although less specific, systemic therapies targeting VEGF, EGFR, or mTOR along with immune checkpoint inhibitors have shown promising efficacy for metastatic FH-deficient tumors, and several clinical trials are ongoing (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…When tumors are relatively small and localized, unique surgical approaches for FH-deficient RCC can be taken. These include immediate resection upon observation, partial nephrectomy with wider margins or radical nephrectomy, regional lymph node dissection, and/or open surgery (11)(12)(13)(14)(15). Although less specific, systemic therapies targeting VEGF, EGFR, or mTOR along with immune checkpoint inhibitors have shown promising efficacy for metastatic FH-deficient tumors, and several clinical trials are ongoing (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…1 Data suggest that hereditary cases can account for anywhere from 2% to 8% of all cases of RCC, with some suggesting this may be an underestimate and could be as high as 38% of cases having a hereditary component. 2 Screening for genetic alterations can provide value for guiding management; specific genetic variants may warrant initial conservative management, with nephronsparing minimally invasive options, while others require more aggressive treatment. 2 Multiple attempts have been made to establish recommendations regarding who should undergo genetic risk assessments.…”
Section: Editorial Commentmentioning
confidence: 99%
“…2 Screening for genetic alterations can provide value for guiding management; specific genetic variants may warrant initial conservative management, with nephronsparing minimally invasive options, while others require more aggressive treatment. 2 Multiple attempts have been made to establish recommendations regarding who should undergo genetic risk assessments. The consensus statement by Bratslavsky et al reported that "For an individual without a renal tumor(s) and first-degree relative(s) with RCC, should genetic risk assessment be offered," 23% of experts said "yes" while 77% said "no."…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous hereditary tumor syndromes that increase the risk of kidney cancer with implications for screening and both surgical and systemic treatments [9]. The AUA (expert opinion), NCCN (level 2a), and EAU (strong) guidelines recommend referral for consideration of germline testing for all patients aged 46 yr with renal cancer, those with multifocal/bilateral renal masses, those with a personal/family history suggestive of a renal cancer syndrome, those with a first-or second-degree relative with a renal cancer or known diagnosis of a familial cancer syndrome, and patients with pathology suggestive of histologic findings [10,11].…”
Section: Kidney Cancermentioning
confidence: 99%